Towards a Sport Professionalization: the Situation of the Player Agents in the Lithuanian Football League A - Mindaugas Gobikas; Vilma Čingienė; Daniel S. Mason (Lithuanian Sports University, 2018)
The aim of the research was to identify and evaluate the peculiarities and necessity of a player agent's profession in the Lithuanian sports sector. The methods of the research: the analysis of a scholarly literature and a standardized interview. 30 Lithuanian Football League A (LFLA) players who did not have a player agent answered the interview's questions. The majority of the LFLA players do not employ a player agent, however they all recognize the necessity of these professionals in the professional sports industry. Low salaries, the lack of information about player agents and their practice, poor player agents' reputation were identiﬁed as the main reasons for not having an agent. Keywords: the work of a player agent, professional sport, Lithuanian Football Leag